Exploring Medical Students’ Readiness for E-Learning and Knowledge Sharing Behaviors in Emergency Remote Learning Environments during Covid-19 - Gunes Korkmaz; Cetin Toraman (Journal of Education in Science, Environment and Health)
The rapid spread of Covid-19 pandemic has profoundly affected the educational practices all over the world and educational institutions sought ways to adapt to this unprecedented situation. The problem was that most of these institutions, educators and students were not ready for online learning environments and the stakeholders were not yet sure about how to share the knowledge in a better way. This study aims to examine the medical students’ readiness for e-learning and knowledge sharing behaviors in online learning environments during Covid-19, and to analyze the relationship between these variables. The study has been designed according to correlational research methodology. The data were collected using “Knowledge Sharing Behavior in Online Learning Environments Scale” and “E-Learning Readiness Self-Assessment Instrument”. 725 medical students participated in the study. Students' readiness for e-learning and knowledge sharing behaviors were analyzed using descriptive statistics, and the relationship between the variables was modeled using multivariate regression equation. The results revealed that the students with high ability to use computer, mobile phone and tablet PC have higher readiness level for e-learning in terms of technology access, technical skills, online relationships, motivation, online skills, importance of success. Similarly, they have a higher level of knowledge sharing behaviors in online learning environments.